Fear inoculation among snake experts - Carlos M. Coelho; Jakub Polák; Panrapee Suttiwan; Andras N. Zsido (BMC Psychiatry, 2021)
Abstract Background Fear acquisition of certain stimuli, such as snakes, is thought to be rapid, resistant to extinction, and easily transferable onto other similar objects. It has been hypothesized that due to increased survival chances, preparedness to instantly acquire fear towards evolutionary threats has been hardwired into neural pathways of the primate brain. Here, we compare participants’ fear of snakes according to experience; from those who often deal with snakes and even suffer snakebites to those unfamiliar with snakes. Methods The Snake Questionnaire-12 (SNAQ-12) and Specific Phobia Questionnaire (SPQ) were administered to three groups of participants with a different level of experience with snakes and snakebites: 1) snake experts, 2) firefighters, and 3) college students. Results This study shows that individuals more experienced with snakes demonstrate lower fear. Moreover, participants who have suffered a snakebite (either venomous or not) score lower on fear of snakes (SNAQ-12), but not of all other potentially phobic stimuli (SPQ). Conclusions Our results suggest that a harmless benign exposure might immunize people to highly biologically prepared fears of evolutionary threats, such as snakes.